Chirality‐Induced Variation in Interaction of Two Similar Copper(II) Coordination Polymers with Calf Thymus DNA: Exploration of Their Antimicrobial Activity and Cytotoxicity. Issue 25 (2nd July 2018) - Khan, Samim; Masum, Abdulla Al; Giri, Pritam; Islam, Md. Maidul; Harms, Klaus; Chattopadhyay, Shouvik
Abstract: Two polynuclear end‐to‐end dicyanamide (dca) bridged copper(II) Schiff base complexes [Cu(L 1 )(μ 1, 5 ‐dca)]n (1 ) and [Cu(L 2 )(μ 1, 5 ‐dca)]n (2 ) {[HL 1 =(1‐(2‐(diethylamino)ethylimino)ethyl) naphthalene‐2‐ol] and [HL 2 =(1‐(2‐(dimethylamino)ethylimino)methyl) naphthalene‐2‐ol]} were synthesized and X‐ray characterized. Complex1 crystallizes in chiral space group C 2 and complex2 crystallizes in achiral space group P 21 /c. Interactions of both complexes with calf thymus DNA (CT DNA) were studied by UV‐vis and circular dichroism spectroscopy. Molecular docking studies were also carried out for both complexes to find their binding affinity using Alpha PMI as the placement methodology. Although docking studies indicated that the binding constants of both complexes with CT DNA were more or less same, UV‐Vis spectral data indicated that the binding constant of complex1 with CT DNA is considerably large compared to that of complex2 . As complex1 is chiral and complex2 is achiral, it may be concluded that the chirality of complex1 played very significant role to binding of chiral DNA molecule. The antimicrobial activity were estimated by the determination of the minimal inhibitory concentration (MIC) using the broth microdilution method. The complexes showed high in vitro cytotoxicity against MDA‐MB 468 cells. Abstract : Two copper(II) Schiff base complexes have been synthesized and characterized. Interactions of both complexes with ct‐DNA were monitored by UV visible spectroscopy. Higher binding propensity for one of the complexes may be correlated with its chirality.